Avaliação de diferentes fotossensibilizadores na terapia fotodinâmica antimicrobiana no tratamento da doença periodontal induzida: estudo in vivo e in vitro. - Sánchez Puetate, Julio Cesar [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
A Terapia Fotodinâmica Antimicrobiana (antimicrobial Photodynamic Therapy – aPDT), tem sido utilizada como uma terapia coadjuvante na doença periodontal (DP). O objetivo deste trabalho foi avaliar os efeitos antimicrobianos da aPDT, com os fotossensibilizadores Hipericina-glucamina (Hy-g) e Ftalocianina-glucamina (Ft-g), no tratamento e progressão da doença periodontal induzida experimentalmente em ratos, assim como sobre um modelo de biofilme multiespécie in vitro. Os micro- organismos avaliados foram Porphyromonas gingivalis (P. gingivalis, ATCC 33277), Aggregatibacter actynomicetemcomitans (A. actynomicetemcomitans, JP2), Fusobacterium nucleatum (F. nucleatum, ATCC25586), e Streptococcus oralis (S. oralis, ATCC 35037). Dois estudos distintos foram conduzidos. No Estudo 1, foi avaliado in vivo a viabilidade dos micro-organismos mediante o modelo da doença periodontal induzida experimentalmente em ratos após 7 dias de indução da DP. Os animais foram divididos em 7 grupos experimentais (n=8): Grupo Controle; Ftalocianina-glucamina (Ft-g); Hipericina-glucamina (Hy-g); LED vermelho (LV, 655nm; 34 J/cm2); LED âmbar (LA, 590nm; 34,10 J/cm2); aPDT 1(aPDT-Hy-g + LA); aPDT 2 (aPDT-Ft-g + LV). Os animais foram eutanasiados com 7 e 30 dias após a aplicação dos tratamentos no período baseline. No Estudo 2, foi avaliado in vitro a viabilidade dos micro-organismos mediante o modelo de biofilme multiespécie, as amostras foram divididas em 8 grupos experimentais: Controle Negativo; Controle Positivo (clorexidina 0,12%); Ftalocianina-glucamina (Ft-g); Hipericina-glucamina (Hy-g); LED Vermelho (LED-V, 660nm; 39,65 J/cm2); LED Âmbar (LED-A, 590nm; 39,30 J/cm2); aPDT 1 (aPDT-Ft-g + LV); aPDT 2 (aPDT-Hy-g + LA), três experimentos independentes foram realizados em triplicata (n=9). Para os dois estudos foi analisada a quantificação individual dos micro-organismos pela técnica de qPCR combinada com Propidium Monoazide (PMA). Os dados foram submetidos a análise estatística (α=0,05). Os resultados do modelo in vivo no período baseline quando comparados os grupos aPDTs com o grupo controle negativo para P. gingivalis foram, no grupo controle (6,89 ± 0,11), aPDT 1 (6,74 ± 0,26), aPDT 2 (5,88 ± 0,42); para F. nucleatum foram, no grupo controle (9,98 ± 0,20), aPDT 1 (9,76 ± 0,42), aPDT 2 (9,10 ± 0,43*); para A. actynomicetemcomitans foram, no grupo controle (9,75 ± 0,54), aPDT 1 (10,25 ± 0,47*), aPDT 2 (9,57 ± 0,14); para So foram, no grupo controle (2,62 ± 0,30), aPDT 1 (2,28 ± 0,30*), aPDT 2 (2,12 ± 0,14*); no período de 7 dias para P. gingivalis foram, no grupo controle (6,08 ± 0,39), aPDT 1 (7,13 ± 0,18*), aPDT 2 (6,73 ± 0,35); para F. nucleatum foram, no grupo controle (8,39 ± 0,27), aPDT 1 (9,45 ± 0,29*), aPDT 2 (9,42 ± 0,11*); para A. actynomicetemcomitans foram, no grupo controle (8,75 ± 0,30), aPDT 1 (8,36 ± 0,27), aPDT 2 (8,44 ± 0,44); para So foram, no grupo controle (2,55 ± 0,26), aPDT 1 (2,66 ± 0,20), aPDT 2 (2,75 ± 0,28); no período de 30 dias para P. gingivalis foram, no grupo controle (6,98 ± 0,31), aPDT 1 (6,95 ± 0,39), aPDT 2 (6,67 ± 0,38); para F. nucleatum foram, no grupo controle (9,18 ± 0,59), aPDT 1 (9,41 ± 0,42), aPDT 2 (9,26 ± 0,33); para A. actynomicetemcomitans foram, no grupo controle (8,75 ± 0,34), aPDT 1 (8,39 ± 0,35*), aPDT 2 (7,80 ± 0,75*); para S. oralis foram, no grupo controle (2,62 ± 0,35), aPDT 1 (2,93 ± 0,44), aPDT 2 (2,98 ± 0,26). Os resultados do modelo in vitro quando comparados os grupos aPDTs com o grupo controle negativo para A. actynomicetemcomitans foram, no grupo controle negativo (8,77 ± 0,93), aPDT 1 (6,74 ± 0,74*), aPDT 2 (9,05 ± 0,70); para F. nucleatum foram, no grupo controle negativo (8,99 ± 0,84), aPDT 1 (7,42 ± 0,52*), aPDT 2 (12,24 ± 0,42*); para P. gingivalis foram, no grupo controle negativo (6,60 ± 0,33), aPDT 1 (5,77 ± 0,58*), aPDT 2 (7,63 ± 0,23); para S. oralis foram, no grupo controle negativo (8,81 ± 0,49), aPDT 1 (8,34 ± 0,65), aPDT 2 (9,78 ± 0,20).

Antimicrobial Photodynamic Therapy (antimicrobial Photodynamic Therapy - aPDT), has been used as an adjunct therapy in periodontal disease (PD). The objective of this work was to evaluate the antimicrobial effects of aPDT, with the photosensitizers Hypericin-glucamine (Hy-g) and Phthalocyanine-glucamine (Ft-g), in the treatment and progression of experimentally induced periodontal disease in rats, as well as on a model of multispecies biofilm in vitro. The microorganisms evaluated were Porphyromonas gingivalis (P. gingivalis, ATCC 33277), Aggregatibacter actynomicetemcomitans (A. actynomicetemcomitans, JP2), Fusobacterium nucleatum (F. nucleatum, ATCC25586), e Streptococcus oralis (S. oralis, ATCC 35037). Two separate studies were conducted. In Study 1, the viability of microorganisms was evaluated in vivo using the periodontal disease model experimentally induced in rats after 7 days of PD induction. The animals were divided into 7 experimental groups (n = 8): Control Group; Phthalocyanine-glucamine (Ft-g); Hypericin-glucamine (Hy-g); Red LED (LV, 655nm; 34 J / cm2); Amber LED (LA, 590nm; 34.10 J / cm2); aPDT 1 (aPDT-Hy-g + LA); aPDT 2 (aPDT-Ft-g + LV). The animals were euthanized 7 and 30 days after the application of the treatments in the baseline period. In Study 2, the viability of microorganisms was evaluated in vitro using the multispecies biofilm model, the samples were divided into 8 experimental groups: Negative Control; Positive Control (0.12% chlorhexidine); Phthalocyanine- glucamine (Ft-g); Hypericin-glucamine (Hy-g); Red LED (LED-V, 660nm; 39.65 J / cm2); Amber LED (LED-A, 590nm; 39.30 J / cm2); aPDT 1 (aPDT-Ft-g + LV); aPDT 2 (aPDT-Hy-g + LA), three independent experiments were carried out in triplicate (n = 9). For both studies, the individual quantification of microorganisms was analyzed using the qPCR technique combined with Propidium Monoazide (PMA). The data were submitted to statistical analysis (α = 0.05). The results of the in vivo model in the baseline period when comparing the aPDTs groups with the P. gingivalis negative control group were, in the control group (6.89 ± 0.11), aPDT 1 (6.74 ± 0.26), aPDT 2 (5.88 ± 0.42); for F. nucleatum, in the control group (9.98 ± 0.20), aPDT 1 (9.76 ± 0.42), aPDT 2 (9.10 ± 0.43 *); for A. actynomicetemcomitans, in the control group (9.75 ± 0.54), aPDT 1 (10.25 ± 0.47 *), aPDT 2 (9.57 ± 0.14); for S. oralis, in the control group (2.62 ± 0.30), aPDT 1 (2.28 ± 0.30 *), aPDT 2 (2.12 ± 0.14 *); in the 7- day period for P. gingivalis, in the control group (6.08 ± 0.39), aPDT 1 (7.13 ± 0.18 *), aPDT 2 (6.73 ± 0.35); for F. nucleatum, in the control group (8.39 ± 0.27), aPDT 1 (9.45 ± 0.29 *), aPDT 2 (9.42 ± 0.11 *); for A. actynomicetemcomitans, in the control group (8.75 ± 0.30), aPDT 1 (8.36 ± 0.27), aPDT 2 (8.44 ± 0.44); for S. oralis, in the control group (2.55 ± 0.26), aPDT 1 (2.66 ± 0.20), aPDT 2 (2.75 ± 0.28); in the 30- day period for P. gingivalis, in the control group (6.98 ± 0.31), aPDT 1 (6.95 ± 0.39), aPDT 2 (6.67 ± 0.38); for F. nucleatum, in the control group (9.18 ± 0.59), aPDT 1 (9.41 ± 0.42), aPDT 2 (9.26 ± 0.33); for A. actynomicetemcomitans, in the control group (8.75 ± 0.34), aPDT 1 (8.39 ± 0.35 *), aPDT 2 (7.80 ± 0.75 *); for S. oralis, in the control group (2.62 ± 0.35), aPDT 1 (2.93 ± 0.44), aPDT 2 (2.98 ± 0.26). The results of the in vitro model when comparing the aPDTs groups with the negative control group for A. actynomicetemcomitans were, in the negative control group (8.77 ± 0.93), aPDT 1 (6.74 ± 0.74 *), aPDT 2 ( 9.05 ± 0.70); for F. nucleatum, in the negative control group (8.99 ± 0.84), aPDT 1 (7.42 ± 0.52 *), aPDT 2 (12.24 ± 0.42 *); for P. gingivalis, in the negative control group (6.60 ± 0.33), aPDT 1 (5.77 ± 0.58 *), aPDT 2 (7.63 ± 0.23); for S. oralis, in the negative control group (8.81 ± 0.49), aPDT 1 (8.34 ± 0.65), aPDT 2 (9.78 ± 0.20).
Evaluation of different photosensitizers in antimicrobial photodynamic therapy in the treatment of induced periodontal disease: in vivo and in vitro study
Keywords: Fotoquimioterapia; Biofilmes; Periodontite; Photochemotherapy; Biofilms; Periodontitis